Gender and Education in the Context of Sustainable Development Goals - Syahmahita Damanik, Fritz Hotman (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
This research article provides a concise overview of the study on "Gender and Education in the Context of Sustainable Development Goals" by employing a Systematic Literature Review (SLR) with the PICO framework. The study investigates how gender-related factors influence educational access, participation, and outcomes within the framework of Sustainable Development Goals, particularly SDG 4 (Quality Education) and SDG 5 (Gender Equality). Using the PICO criteria—Population (diverse gender groups in formal and non-formal education), Intervention (inclusive education policies, empowerment programs, and strategies to reduce gender disparities), Comparison (various international policies and practices), and Outcome (impacts on educational quality and SDG achievement)—the review synthesizes findings from peer-reviewed articles published within the last five years. The results highlight that gender-responsive education policies significantly contribute to enhancing educational quality and promoting equality; however, challenges such as social, economic, and cultural barriers continue to impede progress. The paper concludes with recommendations for strengthening regulatory frameworks, expanding access to education for marginalized groups, and integrating gender equality principles into educational curricula to support sustainable development.